APPLICATION TIPS AND METHODS OF HEALTH CARE EFFECTIVE USING MACROMEDIA FLASH MX - Nining Rahmawati; Diyah Ruri Irawati, SKom, MMSI. Diyah Ruri Irawati, SKom, MMSI. (Jurnal Sistem Informasi, 2007)
In life, we can not avoid an issue of health in our lives. Because health is very important for anyone who has to live healthy thinking patterns. With it to make it easier to find information about the Writing of health is presented to you who care and want to know about the health of yourself, your family and the environment.